Schooling and Travelling Communities Exploring the Spaces of Educational Exclusion - Cudworth, Dave (Springer International Publishing, 2018)
This book calls for a re-thinking of educational provision for Gypsy / Traveller communities. Despite having been recognised by the government and educational providers for over fifty years, underachievement of children from Gypsy / Traveller communities persists. Rather than focusing specifically on access, attendance and attainment, the author provides a structural analysis of the cultural tensions that often exist between Nomadic communities and current school provision based on the interests and values of Sedentarism. The author uses spatial theory as a base upon which to build knowledge and understanding of the educational exclusion of children from Gypsy / Traveller communities, highlighting the social role that space plays within schools. This innovative book will be of interest and value for students and scholars interested in not only education and Gypsy / Traveller communities, but education for minority communities more widely. .